Analisis Hubungan Suhu Permukaan Laut dan Variabilitas Curah Hujan di Kabupaten Paniai dan Manokwari - Faqi, Ekky Amiral; Menggala, Akhdori Alfa (Universitas Muhammadiyah Gorontalo, 2025)
One of climate parameter is rainfall. Rainfall variations is influenced by many factors one of them is Sea Surface Temperature (SST). SST has a significant role in the occurrence of rain. This study aims to analyze the effect of SST to rainfall variations in the Manokwari region which represents a coastal area with a monsoonal rain pattern and Paniai Regency which represents a mountainous area with an equatorial rain pattern. In this study, an analytical method was used with rainfall data with 2017-2021 period from the BMKG Station in Manokwari and Paniai, as well as an analysis of the Nino 3.4 Sea Surface Temperature anomaly reanalysis data from NOAA. The results showed that the rainfall anomaly and SST anomaly in Paniai had an inverse relationship. Rainfall anomaly and SST anomaly in Manokwari generally have a directly proportional relationship. Reviewed from the value of the correlation coefficient, a significant relationship between the SST anomaly and the rainfall anomaly in Paniai and in Manokwari occurs in certain months.